Social Expectations from Education to Fulfill Human Expectations: A Birds Eye-View on Inequality of Higher Education in Border Area: Kachchh: Addressing Challenges in Higher Education in Rural Border Areas (Journal of Advances and Scholarly Researches in Allied Education, 2018)
For the country like India, who is desperately groping to find its place among the powerful economics. Higher education is not less important than the “Sanjeevani” (plamt that has resurrection power). Along with the primary and secondary education, Higher education plays the conspicuous part to transcend the future of the nation from ground to global. It is important to evolve every facet of the country, but as far as the higher education is concerned, it is urban centric. And consequently, the remote part of the country have been cut of the rest. Most of the higher education institutions in border areas lack quality and facilities. And in areas like Kachchh(gujrat), the situation is worse in regard to gross enrolment ratio. This paper covers the issues and tries to cope up with the puzzling circumstances for the student fraternity that rural students of borderarer are suffering.